RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE AND ATTITUDES ABOUT FEEDING PATTERNS WITH THE NUTRITIONAL STATUS OF PRESCHOOL CHILDREN - Zendrato, Angelica Heildi Nartha; Daeli, Selvi Rahmani; Mendrofa, Sri Ardiyanti; Ompusunggu, Fransiska; Silalahi, Elfrida (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Nutrition problems in children remain a serious challenge to health development, including in preschool-aged children. One important factor that influences children’s nutritional status is the role of mothers as primary caregivers. Mothers’ knowledge and attitudes toward nutrition play a crucial role in decision-making to meet their children’s nutritional needs. However, many preschool-aged children still experience malnutrition despite their mothers having sufficient knowledge. This prompted research to examine the relationship between mothers’ knowledge and attitudes toward feeding patterns and the nutritional status of preschool-aged children.Methods: The method used in this study is a quantitative approach with a cross-sectional design using non-probability sampling. The study population consisted of 260 mothers with preschool children, with a sample size of 158 participants. The sampling technique used was random sampling. This study used a questionnaire assessing mothers’ knowledge and attitudes toward the nutrition of preschool-aged children, which had been adopted and modified. Results: The results of the chi-square test showed most respondents had poor knowledge (49.4%), and their attitudes were in the good category (53.8%). Most respondents had good nutritional status (60.1%). The relationship between knowledge about dietary patterns and nutritional status (p-value= 0.777), but attitudes and nutritional status (p-value= 0.003). Conclusion: There was no relationship between knowledge about dietary patterns and the nutritional status of preschool children. However, there was a relationship between attitudes toward dietary patterns and the nutritional status of preschool children. These results emphasise that cognitive aspects need to be expanded with an affective approach.